Surgical rescue: The next pillar of acute care surgery. Issue 2 (February 2017) - Kutcher, Matthew E.; Sperry, Jason L.; Rosengart, Matthew R.; Mohan, Deepika; Hoffman, Marcus K.; Neal, Matthew D.; Alarcon, Louis H.; Watson, Gregory A.; Puyana, Juan Carlos; Bauzá, Graciela M.; Schuchert, Vaishali D.; Fombona, Anisleidy; et al.
Abstract : BACKGROUND: The evolving field of acute care surgery (ACS) traditionally includes trauma, emergency general surgery, and critical care. However, the critical role of ACS in the rescue of patients with a surgical complication has not been explored. We here describe the role of "surgical rescue" in the practice of ACS. METHODS: A prospective, electronic medical record-based ACS registry spanning January 2013 to May 2014 at a large urban academic medical center was screened by ICD-9 codes for acute surgical complications of an operative or interventional procedure. Long-term outcomes were derived from the Social Security Death Index. RESULTS: Of 2, 410 ACS patients, 320 (13%) required "surgical rescue": most commonly, from wound complications (32%), uncontrolled sepsis (19%), and acute obstruction (15%). The majority of complications (85%) were related to an operation; 15% were related to interventional procedures. The most common rescue interventions required were bowel resection (23%), wound debridement (18%), and source control of infection (17%); 63% of patients required operative intervention, and 22% required surgical critical care. Thirty-six percent of complications occurred in ACS primary patients ("local"), whereas 38% were referred from another surgical service ("institutional") and 26% referred from another institution ("regional"). Hospital length of stay was longer, and in-hospital and 1-year mortalities were higher in rescue patients compared with those without a complication. Outcomes were equivalent between "local" and "institutional" patients, but hospital length of stay and discharge to home were significantly worse in "institutional" referrals. CONCLUSION: We here describe the distinct role of the acute care surgeon in the surgical management of complications; this is an additional pillar of ACS. In this vital role, the acute care surgeon provides crucial support to other providers as well as direct patient care in the "surgical rescue" of surgical and procedural complications. LEVEL OF EVIDENCE: Epidemiological study, level III; therapeutic/care management study, level IV.